School leadership in between daily tasks and strategic school improvement – theses from a qualitative workplace analysis from the perspective of key actors - Kruse, Christoph; Stephan Gerhard (Swiss Journal of Educational Research, 2021)
With a multi-perspective approach, we explore tasks and interfaces in school management regarding their general arrangement and functionality. Results of 18 structured interviews with school leaders, secretary staff and members of school boards are presented and discussed. It can be shown that stress, workload and time pressure convey dysfunctional effects: Hence, the key actors prioritise continuity and provision of essential functioning of their schools. Therefore, tasks concerning quality management and school improvement as well as personnel management become systematically neglected. Furthermore, we identify various role-related ambiguities and potentials for improving task distribution. When reflecting on the derived theses, it is argued that interfaces constitute a vital impact on school management.